Pendidikan Kesehatan Reproduksi Bagi Remaja (Literatur Review) - Hastuti Marlina; Nizwardi Jalinus; Rusnadi Rahmat (Universitas Negeri Padang, 2018)
The problem of teenagers in that world associated with early health, early circulation, difficult cancer, HIV / AIDS and increased STIs. The writing of this article is to know and examine the efforts and programs that have been conducted by various countries in providing information on issues relating to the three issues of adolescent reproductive health (Sexuality, HIV / AIDS and Drugs). The method used in the journal using EBSCO, Proquest, Sciencedirect, google scholar published from 2002 to 2018. The result of the literature review is the knowledge of sexual health education portrait for which has been done by various countries namely: Integration of Sexual Education in all strata of education, Counseling Sexual Education by Specialist Doctors, School-based Counseling is accompanied by Parents. The correlation of sex education in schools by teachers wants to apply in the home associated with parents despite the need for regular consultation to specialist doctors such as doctors, pediatricians and doctors of venereal diseases. Sex education on reproductive health has been done in various countries proven to reduce the three problems of adolescent reproductive health Keywords: Education, Sex, Teenagers